Sibolga Coastal Nominal Phrases - Siti Aisyah; Mulyadi Mulyadi (Budapest International Research and Critics University, 2023)
This study discusses the structure of noun phrases in Pesisir Sibolga language. The main objective of the research is to find noun phrases in Pesisir Sibolga language which are used generally by the speaking community. The structure is analyzed based on X-bar theory, which is a theory that specifically discusses the problem of phrase structure. This study uses a qualitative research design with interview methods. The research data is primary data. Data presentation was carried out through interviews with native speakers of the Sibolga coastal language using in-depth interviews. The resource persons are people who live in the Barus sub-district and the city of Sibolga. In this study, seven patterns of noun phrases were found, namely:FN àN'; Spes, FNàN'; N, FNàN'; V, FNàN'; Adj, FNàN'; FP, FNàFNum; N, FNàN'; Kl Rail; Spes.